A framework for prioritizing areas for conservation in tropical montane cloud forests. Issue 1 (2nd January 2018) - Hermes, Claudia; Segelbacher, Gernot; Schaefer, H. Martin
ABSTRACT: Tropical cloud forests are under severe distress, as deforestation leads to forest fragmentation and degradation. This represents a severe threat to small-ranged, forest-dependent species, as they are at risk of losing habitat and connectivity between populations. These detrimental effects are aggravated by upslope range shifts caused by climate change, as further habitat loss is expected. To mitigate these threats, the preservation of habitat and connectivity becomes necessary. Here, we present a novel framework for identifying future key areas offering high-quality habitat and connectivity. The framework combines data on the composition of forests, their configuration in the landscape, as well as dispersal abilities and altitudinal range for several focal species. Importantly, the framework integrates projections of future range shifts. Thus, it prioritizes a network of areas with high-conservation value robust to climate change. We applied the framework to the cloud forest in Ecuador, using two endemic bird species to identify areas for mitigating the adverse effects of climate change. Our approach allows targeting reforestation measures effectively to areas of high-conservation value. The framework presented here can be applied to different ecosystems and geographical locations, and therefore contribute to making informed decisions about the implementation of robust conservation measures.